Phagocytic intracellular digestion in amphioxus (Branchiostoma). Issue 1880 (6th June 2018) - He, Chunpeng; Han, Tingyu; Liao, Xin; Zhou, Yuxin; Wang, Xiuqiang; Guan, Rui; Tian, Tian; Li, Yixin; Bi, Changwei; Lu, Na; He, Ziyi; Hu, Bing; et al.
Abstract : The digestive methods employed by amphioxus ( Branchiostoma )—both intracellular phagocytic digestion and extracellular digestion—have been discussed since 1937. Recent studies also show that epithelial cells lining the Branchiostoma digestive tract can express many immune genes. Here, in Branchiostoma belcheri, using a special tissue fixation method, we show that some epithelial cells, especially those lining the large diverticulum protruding from the gut tube, phagocytize food particles directly, and Branchiostoma can rely on this kind of phagocytic intracellular digestion to obtain energy throughout all stages of its life. Gene expression profiles suggest that diverticulum epithelial cells have functional features of both digestive cells and phagocytes. In starved Branchiostoma, these cells accumulate endogenous digestive and hydrolytic enzymes, whereas, when sated, they express many kinds of immune genes in response to stimulation by phagocytized food particles. We also found that the distal hindgut epithelium can phagocytize food particles, but not as many. These results illustrate phagocytic intercellular digestion in Branchiostoma, explain why Branchiostoma digestive tract epithelial cells express typical immune genes and suggest that the main physiological function of the Branchiostoma diverticulum is different from that of the vertebrate liver.